2014
DOI: 10.1080/00958972.2014.961442
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(II), nickel(II), and copper(II) complexes of 14-membered hexaazamacrocycles: synthesis and characterization

Abstract: Cobalt(II), nickel(II), and copper(II) complexes containing 5,12-di(4-bromophenyl)-7, 14-dimethyl-1,2,4,8,9,11-hexaazacyclotetradeca-7,14-diene-3,10-dione (H 2 L 1 ) and 5,12-diphenyl-7,14-dimethyl-1,2,4,8,9,11-hexaazacyclotetradeca-7,14-diene-3,10-dione (H 2 L 2 ) have been synthesized. All complexes were characterized by elemental analysis, MALDI TOF-MS spectrometry, and electronic absorption spectroscopy. The crystal structures of two compounds, [Cu 2 (H 2 L 1 )Cl 4 ] n and [NiL 2 ], were determined by X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…0.025 Å) longer than Ni–N3 in nickel­(II) complex 4 . The difference between these two bonds in the nickel­(II) complex with IX where Ar = Ph (Scheme ) with Ni–N hydrazine = 1.900(11) Å and Ni–N amide = 1.860(11) Å is not significant . In the case of copper­(II) complexes 2·EtOH and 5 the bond length difference is quite significant and amounts to ca.…”
Section: Results and Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…0.025 Å) longer than Ni–N3 in nickel­(II) complex 4 . The difference between these two bonds in the nickel­(II) complex with IX where Ar = Ph (Scheme ) with Ni–N hydrazine = 1.900(11) Å and Ni–N amide = 1.860(11) Å is not significant . In the case of copper­(II) complexes 2·EtOH and 5 the bond length difference is quite significant and amounts to ca.…”
Section: Results and Discussionmentioning
confidence: 96%
“…In contrast, the nickel(II) complex of trans-IX (Ar = Ph) is involved in strong intermolecular interactions of lactam groups via centrosymmetric N−H•••O hydrogen bonds, as shown in Figure S15. 57 As mentioned previously, this might be a reason for the low solubility of the nickel(II) complexes in common organic solvents and water.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Powder X-ray diffraction analysis 13a and DFT calculations showed that the internal cavity of macrocycles 1 is able to chelate various metal cations through the N1, N4, N8, and N11 atoms. Indeed, the neutral complex of dianion of 1 (R = Ph, R 1 = H) with Ni(II) was obtained, 14 demonstrating that hexaaza macrocycles 1 can serve as novel tetradentate ligands for metal ions. However, progress in this area was hampered by the low availability of macrocycle precursors 2 which were prepared in four steps from ethyl carbamate involving α-amidoalkylation of sodium acetylacetonates with ethyl N-(tosylmethyl)carbamates.…”
mentioning
confidence: 99%
“…46,47 Furthermore, Nam, Fukuzumi, and others have recently extended the applications of TAML compounds to other applications such as oxidative C-H activation by high-valent Co and Ni complexes. 40,[48][49][50][51][52][53][54][55][56][57] These seminal studies highlight the oxidative robustness of TAML systems, but also underscore the paucity of reports on the reductive catalytic activity of these potentially nucleophilic late transition metal -ate complexes.…”
Section: Introductionmentioning
confidence: 99%